Benzoates intakes from non-alcoholic beverages in Brazil, Canada, Mexico and the United States. Issue 9 (2nd September 2017) - Martyn, Danika; Lau, Annette; Darch, Maryse; Roberts, Ashley
ABSTRACT: Food consumption data from national dietary surveys were combined with brand-specific-use levels reported by beverage manufacturers to calculate the exposure to benzoic acid and its salts (INS Nos 210–213) from non-alcoholic beverages in Brazil, Canada, Mexico and the United States. These four jurisdictions were identified as having some of the most prevalent use of benzoates in beverages globally. Use levels were weighted according to the brand's market volume share in the respective countries. Benzoates were reported to be used primarily in 'water-based flavoured drinks' (Codex General Standard for Food Additives (GSFA) category 14.1.4). As such, the assessments focused only on intakes from these beverage types. Two different models were established to determine exposure: probabilistic (representing non-brand loyal consumers) and distributional (representing brand-loyal consumers). All reported-use levels were incorporated into both models, including those above the Codex interim maximum benzoate use level (250 mg kg −1 ). The exception to this was in the brand-loyal models for consumers of regular carbonated soft drinks (brand loyal category) which used (1) the interim maximum use level for beverages with a pH ≤ 3.5 and (2) all reported use levels for beverages pH > 3.5 (up to 438 mg kg -1 ). The estimated exposure levels using both models were significantly lower than the ADI established for benzoates at the mean level of intake (4–40% ADI) and lower than – or at the ADI only for toddlers/children – at the 95th percentile (23–110% ADI). The results rendered in the models do not indicate a safety concern in these jurisdictions, and as such provide support for maintaining the current Codex interim maximum benzoate level of 250 mg kg −1 in water-based beverages.